2015
DOI: 10.1128/aac.04853-14
|View full text |Cite
|
Sign up to set email alerts
|

Ambush of Clostridium difficile Spores by Ramoplanin: Activity in an In Vitro Model

Abstract: bClostridium difficile infection (CDI) is a gastrointestinal disease caused by C. difficile, a spore-forming bacterium that in its spore form is tolerant to standard antimicrobials. Ramoplanin is a glycolipodepsipeptide antibiotic that is active against C. difficile with MICs ranging from 0.25 to 0.50 g/ml. The activity of ramoplanin against the spores of C. difficile has not been well characterized; such activity, however, may hold promise, since posttreatment residual intraluminal spores are likely elements … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 30 publications
1
17
0
Order By: Relevance
“…Persistent fidaxomicin activity prevented vegetative outgrowth and toxin production in batch culture, and similar observations were also made for ramoplanin [93] and oritavancin [95]. It is likely that fidaxomicin adheres to the exosporium of C. difficile (as for ramoplanin [96]), potentially as a result of electrostatic charges resulting from cross-linkages on the spore surfaces. The presence of the exosporium can increase hydrophobicity of C. difficile spores, affecting adherence to cells [84].…”
Section: Treatment Agents and Sporessupporting
confidence: 63%
“…Persistent fidaxomicin activity prevented vegetative outgrowth and toxin production in batch culture, and similar observations were also made for ramoplanin [93] and oritavancin [95]. It is likely that fidaxomicin adheres to the exosporium of C. difficile (as for ramoplanin [96]), potentially as a result of electrostatic charges resulting from cross-linkages on the spore surfaces. The presence of the exosporium can increase hydrophobicity of C. difficile spores, affecting adherence to cells [84].…”
Section: Treatment Agents and Sporessupporting
confidence: 63%
“…Theoretically, nisin→HPCD should not enhance the inactivation of the spores since nisin at room temperature cannot act on the spores. Possible explanation for nisin→HPCD enhanced inactivation was probably due to the adherence of nisin to the surface of spores after nisin treatment ( Chilton et al, 2013 ; Kraus et al, 2015 ), and the remaining nisin played an enhanced inactivation of the spores. Its action mode was similar to that of HPCD + nisin.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown to be nonabsorbable, and to bind to spores and kill vegetative C. difficile cells in vitro . This may indicate a potential use for ramoplanin as a preventative measure to reduce risk of initial disease or reduce recurrence by binding to spores and then killing the ones that germinate . A phase II trial comparing treatment using ramoplanin versus vancomycin for CDI showed similar clinical response rates with 400 mg ramoplanin (71% versus 78%) and similar sustained clinical response rates (83% 200 mg ramoplanin, 85.2% 400 mg ramoplanin, and 85.7% vancomycin).…”
Section: Areas For Improvement and Targets For Emerging Therapiesmentioning
confidence: 96%